To snoop or not to snoop? - Katschke, Judy; Kase, Larry Ronkin, Joel (Parachute Publ. New York, 1999)
Cool! Mary-Kate and Ashley have a new telescope. Their father bought it so they could learn about the stars. The twins have a better idea, though: they're going to spy on their neighbors! But the spying turns serious when Mary-Kate sees something she shouldn't. Something that spells big trouble for the twins ..